2020
DOI: 10.1111/ppe.12643
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal thyroid‐stimulating hormone and association with attention‐deficit/hyperactivity disorder

Abstract: Background Normal brain development is dependent on maternal, fetal and neonatal thyroid function. Measuring neonatal thyroid‐stimulating hormone (TSH) 48‐72 hours after birth screens for congenital hypothyroidism, allowing early treatment to avoid serious impairment. However, even within sub‐clinical ranges, disrupted thyroid homeostasis during brain development has been linked to adverse neurodevelopmental outcomes, including attention‐deficit/hyperactivity disorder (ADHD). Objectives To estimate the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Overall, our results support the notion that lower serum TSH may be related to a higher risk for ADHD in children but not adolescents. These findings agree with recent work by Villanger et al who reported that ADHD risk appeared to be elevated among newborns with low TSH levels after analyzing TSH concentrations below 10 mIU/L in 405 ADHD cases and 1092 controls 37 .…”
Section: Discussionsupporting
confidence: 93%
“…Overall, our results support the notion that lower serum TSH may be related to a higher risk for ADHD in children but not adolescents. These findings agree with recent work by Villanger et al who reported that ADHD risk appeared to be elevated among newborns with low TSH levels after analyzing TSH concentrations below 10 mIU/L in 405 ADHD cases and 1092 controls 37 .…”
Section: Discussionsupporting
confidence: 93%
“…It is important, also, to consider that excessive treatment in CH patients seems to be associated to unfavorable cognitive outcomes. There are reports of an increase in cases of attention deficit hyperactivity disorder and even a decrease in intelligence quotient related to excessive treatment [46][47][48]. There is yet no consensus on this subject, more research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, excessive treatment in CH patients appears to be linked to unfavorable cognitive outcomes [ 46 , 47 , 48 ]. There is still no consensus on this matter; further research is needed.…”
Section: Discussionmentioning
confidence: 99%